El software educativo jclic para mejorar el ámbito de relaciones lógico-matemáticas en los niños de preparatoria de la escuela de educación básica rosa Josefina Burneo de Burneo de la ciudad de loja, en el periodo 2019-2020. - Yangari Macas, María Leonela (2020)
The thesis entitled: JCLIC EDUCATIONAL SOFTWARE TO IMPROVE THED FIEL OF LOGICAL-MATHEMATICAL RELATIONS IN ELEMENTARY SCHOOL CHILDREN; OF THE ELEMENTARY SCHOOL ROSA JOSEFINA BURNEO DE BURNEO FROM THE CITY OF LOJA IN THE PERIOD 2019-2020. Its general objective was to identify whether the usage of the educational software JClic helps to improve the field in logicalmathematical relationships in elementary school children. Scientific, descriptive, analyticalsynthetic and inductive-deductive methods were used for its development, and the techniques and instruments used in the research were: a survey applied to 3 teachers and EVAMAT-0 aimed at 24 children aged from 5 to 6 which constituted the study sample. The results showed that in the pre-test it that 75% of children had insufficient level in geometry, 100% in quantity and counting and 71% in problem solving had deficient level. To improve to solve the problem area a proposal based on didactic and interactive activities that once executed and evaluated with the post test, significantly optimized the scope of mathematical logical relationships, the insufficient level was reduced to 8% in geometry and the deficient level at 25% in in quantity and counting and at 8% in problem solving; concluding that used continuously in the classroom, educational software JClic allowed to improve mathematical logical relations, favoring concentration in the child, the capacity of abstraction, discrimination, analysis, argumentation, understanding and the ability to solve problems.